2016
DOI: 10.1016/j.lwt.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The potential of zein nanoparticles to protect entrapped β-carotene in the presence of milk under simulated gastrointestinal (GI) conditions

Abstract: a b s t r a c tThe addition of nanoentrapped b-carotene in milk is proposed as a valid method to improve stability and enhance antioxidant activity of b-carotene during GI transit. This study focused on two types of delivery systems, nanoparticles and nanoemulsions, and compared their ability to enhance the physicochemical stability and antioxidant activity of b-carotene in the presence of milk under simulated GI conditions. bCarotene-loaded zein nanoparticles and nanoemulsion, stabilized by pluronic F127 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Recently, zein nanoparticles have been loaded with different compounds such as resveratrol (Liang et al, 2018), curcumin (Zou et al, 2016), epigallocatechin gallate (Donsì, Voudouris, Veen, & Velikov, 2017), rutin (Zhang & Zhao, 2017), and β-carotene (Chuacharoen & Sabliov, 2016); these studies showed that this protein matrix possesses a high capability to encapsulate these nutraceutical compounds. Furthermore, antioxidant activity and bioaccessibility increase and chemical degradation decreases in the gastrointestinal tract; therefore, its high bioactivity may be compared with unencapsulated compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, zein nanoparticles have been loaded with different compounds such as resveratrol (Liang et al, 2018), curcumin (Zou et al, 2016), epigallocatechin gallate (Donsì, Voudouris, Veen, & Velikov, 2017), rutin (Zhang & Zhao, 2017), and β-carotene (Chuacharoen & Sabliov, 2016); these studies showed that this protein matrix possesses a high capability to encapsulate these nutraceutical compounds. Furthermore, antioxidant activity and bioaccessibility increase and chemical degradation decreases in the gastrointestinal tract; therefore, its high bioactivity may be compared with unencapsulated compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Zein nanoparticle encapsulation protected resveratrol from isomerization by UV light (Davidov-Pardo, Joye, Espinal-Ruiz, & McClements, 2015), and increased its oral bioavailability (Penalva, Esparza, Larraneta, Gonzalez-Navarro, Gamazo, & Irache, 2015). Zein nanoparticles have also been shown to be useful for encapsulating other types of hydrophobic nutraceuticals, including curcumin (Patel, Hu, Tiwari, & Velikov, 2010;Zou, Zheng, Zhang, Zhang, Liu, Liu, et al, 2016), retinol (Park, Park, & Kim, 2015), peppermint oil (Chen & Zhong, 2015), quercetin (Patel, Heussen, Hazekamp, Drost, Velikov, 2012) and carotenoids (Chuacharoen & Sabliov, 2016a, 2016b.…”
Section: Introductionmentioning
confidence: 99%
“…Zein nanoparticles coated with chitosan were also found to provide protection of vitamin E in simulated gastrointestinal tract . For β‐carotene, several recent studies have explored the potential for improving the delivery and bioactivity of β‐carotene through encapsulation in zein particles, or fibers or complex particles …”
Section: Emerging Application Of Functional and Engineered Food Colloidsmentioning
confidence: 99%